IDC golf-ball structured thin films: preparation, characterization and photodiode properties. Issue 59 (3rd June 2016) - Suresh, R.; Ponnuswamy, V.; Sankar, C.; Manickam, M.; Mariappan, R.
Abstract : Uniform and well-dispersed IDC (indium doped cerium oxide) films are successfully deposited by Nebulizer Spray Pyrolysis (NSP) technique. Abstract : Uniform and well-dispersed IDC (indium doped cerium oxide) films are successfully deposited by Nebulizer Spray Pyrolysis (NSP) technique. Cubic fluorite crystallites are detected by an X-ray diffraction pattern with a preferred orientation along the (200) direction. The In concentration affects the crystallinity and structural parameters like crystallite size, texture coefficient, lattice constant and dislocation density. The transmittance decreases with increasing In concentration up to 15% and then increases due to the presence of covalent bonds between cerium and an oxygen additive at the shortest wavelengths. PL spectra revealed that three consistent sharp and broad peaks are observed at 394 (3.14 eV), 425 (2.91 eV) and 579 nm (2.14 eV), which correspond to near band edge emission (NBE) at the UV region and blue and red deep level emission (DLE) in the visible region, respectively. Large agglomerated ring and white spherical crystallites are obtained with a typical size in the range of 93–128 nm. Satellites are caused by the facilitation of ligand (O 2p) to metal (Ce 4f) charge transfer by primary and main photoionization processes, which indicates that the valance states of Ce 3+ (16.7%) and Ce 4+ (36.4%) have entered in to the CeO2 lattice sites. I – V characteristics show the rectifying nature of this hetero-junction with a typical forward to reverse current ratio of ∼7 in the range −3 to +3 V. The turn-on voltage of the hetero-junction is found to be ∼1.5 V. The transient photocurrent behavior indicates that the device has good stability and quick response and suggests that the prepared heterojunction device can be used as a white light photodetector and for UV detector applications.